Solution Structure of the C-terminal Domain of A20, the Missing Brick for the Characterization of the Interface between Vaccinia Virus DNA Polymerase and its Processivity Factor. Issue 13 (25th June 2021) - Bersch, Beate; Tarbouriech, Nicolas; Burmeister, Wim P.; Iseni, Frédéric
Graphical abstract: Highlights: The C-terminal domain of the poxvirus processivity factor A20 shows a new fold. Poxvirus-specific inserts 0 and 3 of the DNA polymerase E9 are the A20 binding site. On A20, the interface features a central hydrophobic leucine-binding pocket. The interface is highly conserved within the chordopoxvirinae subfamily. Processivity factor binding differs from all other family B DNA polymerases. Abstract: Poxviruses are enveloped viruses with a linear, double-stranded DNA genome. Viral DNA synthesis is achieved by a functional DNA polymerase holoenzyme composed of three essential proteins. For vaccinia virus (VACV) these are E9, the catalytic subunit, a family B DNA polymerase, and the heterodimeric processivity factor formed by D4 and A20. The A20 protein links D4 to the catalytic subunit. High-resolution structures have been obtained for the VACV D4 protein in complex with an N-terminal fragment of A20 as well as for E9. In addition, biochemical studies provided evidence that a poxvirus-specific insertion (insert 3) in E9 interacts with the C-terminal residues of A20. Here, we provide solution structures of two different VACV A20 C-terminal constructs containing residues 304–426, fused at their C-terminus to either a BAP (Biotin Acceptor Peptide)-tag or a short peptide containing the helix of E9 insert 3. Together with results from titration studies, these structures shed light on the molecular interface between the catalytic subunit and the processivity factor component A20. The interface comprises hydrophobic residues conserved within the Chordopoxvirinae subfamily. Finally, we constructed a HADDOCK model of the VACV A20304-426 -E9 complex, which is in excellent accordance with previous experimental data.